2011
DOI: 10.3892/ol.2011.534
|View full text |Cite
|
Sign up to set email alerts
|

Plasma epidermal growth factor receptor mutation analysis and possible clinical applications in pulmonary adenocarcinoma patients treated with erlotinib

Abstract: Abstract. Tumor epidermal growth factor receptor (EGFR) mutation analysis is significant for making treatment decisions for metastatic pulmonary adenocarcinoma. However, less than half of patients have adequate tumor samples for mutation analysis. Patients with adenocarcinoma of the lungs who were due to receive erlotinib treatment were included in the present study. Tumor EGFR mutation status was analyzed using DNA sequencing. Plasma specimens from the patients were collected prior to erlotinib treatment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Subsequent studies have attempted to confirm these results in a larger case series (75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89). Using different methodologies, results of the majority of those studies identified identical serum/plasma, with tissue EGFR mutations being reported in >70% of patients (74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89) (Table I).…”
Section: Biological Samples Suitable For Molecular Characterisationmentioning
confidence: 62%
“…Subsequent studies have attempted to confirm these results in a larger case series (75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89). Using different methodologies, results of the majority of those studies identified identical serum/plasma, with tissue EGFR mutations being reported in >70% of patients (74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89) (Table I).…”
Section: Biological Samples Suitable For Molecular Characterisationmentioning
confidence: 62%
“…The participants in 12 included studies 14 18 , 20 , 31 33 , 35 , 41 , 42 were in stages III–IV and 6 studies 19 , 27 , 37 , 40 , 43 , 44 in I–IV. Thirteen studies 14 , 15 , 18 20 , 28 , 31 , 35 38 , 42 , 44 tested EGFR mutations in plasma and 12 studies 16 , 17 , 27 , 29 , 30 , 32 34 , 39 41 , 43 in serum. Direct sequencing and scorpion amplification refractory mutation system (SARMS) were the main methods used for mutation test, which were adopted in 8 16 19 , 28 , 30 , 39 , 40 and 7 18 , 29 , 34 36 , 38 , 41 studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies 14 , 16 19 , 28 , 30 , 38 , 41 with a total of 564 patients contributed to the meta-analysis of EGFR mutations (exons 19 and 21) and survival. The pooled HR for PFS was larger in blood (HR: 0.72; 95% CI 0.64–0.80) than in tumor tissue (HR: 0.57; 95% CI 0.39–0.85) (Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, a lot of retrospective studies have indicated that detection of driver gene mutations in ctDNA of patients with NSCLC is feasible and reliable [63][64][65][66] and can represent a good predictor of clinical response with relevant implications for patient management. In particular for advanced NSCLCs, detection of EGFR L858R mutations in cfDNA can be performed using several platforms with a high sensitivity [67]. An additional recent study from Marchetti et al provides the first strong correlation between the EGFR copy number mutation detection in the first days of treatment and clinical response to TKI treatments with relevant implications for NSCLCs management [68].…”
Section: Circulating-free Dnamentioning
confidence: 99%